Cerium Oxide Polishes Lithium Disilicate Glass Ceramic via a Chemical–Mechanical Process - Yamockul, Suparaksa; Thamrongananskul, Niyom (European Journal of Dentistry, 2022)
Objective The aim of the present study was to evaluate the chemical–mechanical polishing (CMP) effect of cerium oxide (ceria [CeO2]) as an abrasive to polish lithium disilicate glass ceramic.Materials and Methods For the polishing experiment, 22 lithium disilicate glass ceramic samples were prepared, polished with sandpaper using a polishing machine, their surface roughness (Ra) was measured using a profilometer, and they were randomly divided into two groups (n = 10). The samples were polished for 30 seconds with ceria paste with different ratios of deionized water:ceria by weight: 1:0.5 (C0.5) and 1:1 (C1) according to their group and the Ra values were determined. The Ra measurement was repeated after an additional 30 seconds of polishing until 120 seconds of polishing had been performed. The surface images of the postpolishing (120 seconds) samples were obtained using scanning electron microscopy (SEM) to evaluate the surface morphology. For the adsorption experiment, 10 lithium disilicate glass ceramic specimens were prepared and soaked in 50-mL deionized water. After 24 hours, the specimens were removed. Each liquid sample was divided in two halves. The first half was stored and ceria particles were added into the second half. After 24 hours, the solutions were filtered. The silicon concentration in the liquid samples was analyzed using inductively coupled plasma-optical emission spectrometry.Statistical Analysis The difference in mean Ra value between groups was analyzed using two-way repeated analysis of variance (ANOVA) and the difference in mean silica concentrations before and after adding ceria particles was analyzed using the paired t-test. A p-value of <0.05 was considered statistically significant.Results Ra decreased as the ratio of ceria and polishing time increased. The surface morphology of the samples analyzed by SEM corresponded with their Ra values. The mean silicon concentration after adding ceria particles was significantly decreased (p < 0.05).Conclusion Using a ceria-polishing paste to polish lithium disilicate glass ceramic generates a significantly smoother surface compared with baseline roughness. Moreover, CeO2 has a mechanical action and chemical reaction with lithium disilicate glass ceramic. Therefore, it can be used as a CMP paste to create a smooth surface.
Keywords: cerium oxide; chemical–mechanical polishing; lithium disilicate; polishing paste